Improvement in patient-reported outcomes of varicose veins following treatment with polidocanol endovenous microfoam. (June 2017) - Lal, Brajesh K; Mallick, Rajiv; Wright, David
Objective: To evaluate the relationship between patient-reported symptoms and functional and psychological impact of varicose veins following treatment with polidocanol endovenous microfoam (PEM) 1%. Methods: Data were pooled from two randomized trials on VV treatment. Wilson–Cleary health outcomes path model was applied to evaluate impact of VVSymQ™ symptom score improvement on modified VEINES-QOL/Sym functional and psychological scores. Change scores were evaluated for (i) PEM 1% versus placebo groups and (ii) quartiles of symptom improvement. Cumulative distribution function curves were generated to compare percentage of patients with various levels of functional and psychological improvement including clinically meaningful improvement across two treatment groups. Multivariable regression models of change scores and clinically meaningful changes were estimated. Results: In 221 patients (109 PEM 1%; 112 placebo), PEM 1% was associated with median improvements of 2.5 points and 4.0 points on the m-VEINES-QOL/Sym functional limitations and m-VEINES-QOL/Sym psychological limitations scores, compared to 0 and 1.0 point improvements, respectively, for placebo. Cumulative distribution function curves revealed that 20–30% more patients in PEM 1% group achieved clinically meaningful functional and psychological improvement versus placebo group. Conclusions: Patients with above-average symptom improvement had better functional and psychological improvement. PEM 1% treatment had higher odds of clinically meaningful functional and psychological improvement.